The Bioreactor – an Innovative Method of Disposal of Solid Waste - Kaszubska, Mirosława; Wzorek, Małgorzata (Economic and Environmental Studies, 2020)
The paper presents a novel method of rational management of solid waste, namely an example of a modern landfill with enhanced leachate recirculation – a bioreactor landfill. The aim of the paper was to compare modern solutions concerning waste storage with traditional methods in terms of sustainability. The comparison was drawn as a result of conducting literature research and an independent analysis of the data obtained. A number of advantages was presented resulting from using technologies with enhanced leachate recirculation in environmental, social, and economic terms. The superiority of modern technologies of waste management over conventional technologies was clearly stated as a result of the analyses performed.